The Fossilization: What Initial Representations of Future Instructors? - Chmanti-Houari, Imane; Hassani, Mohammed Oudrhiri (Universitas Majalengka, 2024)
Previous research has shown the influence of teachers' initial representations on their assimilation and transmission of scientific concepts to students. In this regard, the aim of the present study is to identify the difficulties faced by future Life and Earth Sciences (LES) teachers in assimilating the concept of fossilization, particularly those related to the mobilization of time and space. Using a mixed-methods approach, we designed a questionnaire that was administered to 30 trainee teachers at the RCJET in Fez, selected by simple random sampling. The data was processed using statistical data processing software (answers to closed questions) and the content analysis method (answers to open and semi-open questions). Various types of obstacles to the mobilization of time and space were detected. The inability to apply the principle of actualism. The conception of the evolution of fossilization processes outside the space-time framework. The inability to conceive fossilization as a contingent and exceptional phenomenon, requiring a long time, difficult to observe with the naked eye, difficult to experiment due to their taking place in different palaeogeographic sites. They also raised the need for special training in geology. As a result, we are proposing an increase in the number of hours spent on practical work, the scheduling of geological field trips, the development of new methods and approaches, and the integration of Information and Communication Technologies (ICT). In order to generalise and validate its results, although they were significant, our research will be extended to a larger sample, and in other countries.